ANALISIS PENGGUNAAN DANA BEASISWA BERPRESTASI PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Rusli, Ariwibowo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The title of this research is analysis of the use outstanding scholarship fund to the student of economic education study programin Teacher Training and Education Faculty of Tanjungpura University, with the problem is how the student of economic education study program use the outstanding scholarship fund? The aim of this research is to know how the student of economic education study program use the outstanding scholarship fund. This research used descriptive methodology, in qualitative research. The sample of this research are seven students of economic education study program who receive the PPA scholarship. The result of this research is the use of PPA scholarship is still not optimal for their academics need. They use the fund for their personal needs, such as buy the new bag, clothes, shoes and smartphone which the cost are greater than their academics need, such as printing their task, photocopy and buy the stationery for their college need. Keywords: The Use, Scholarship Fund, Not Optimal, College Student